2021
DOI: 10.1080/10790268.2021.1970885
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a virtual service delivery model to support physical activity engagement during the COVID-19 pandemic for those with spinal cord injury

Abstract: Background The current pandemic has reduced access to safe, monitored physical activity (PA) programs for persons with spinal cord injury (SCI). The use of telerehabilitation has the potential for continuing activity engagement without risking virus exposure. The present study evaluates the feasibility and efficacy of an online group-based PA program for persons with SCI. Methods This preliminary pre–post study delivered an online group-based PA program to persons with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In recent years, it has been demonstrated that using telerehabilitation can result in considerable clinical gains; as a result, it appears to be on par with traditional clinical rehabilitation treatments [ 18 ]. For example, it is shown that with the contribution of online exercises, older adults with spinal cord injury can develop their well-being and experience greater life satisfaction during times like pandemics and when faced with challenges regarding in-person exercise programs [ 19 ]. As an example, an online Pilates exercise program was previously shown to improve trunk proprioception and muscle endurance significantly [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been demonstrated that using telerehabilitation can result in considerable clinical gains; as a result, it appears to be on par with traditional clinical rehabilitation treatments [ 18 ]. For example, it is shown that with the contribution of online exercises, older adults with spinal cord injury can develop their well-being and experience greater life satisfaction during times like pandemics and when faced with challenges regarding in-person exercise programs [ 19 ]. As an example, an online Pilates exercise program was previously shown to improve trunk proprioception and muscle endurance significantly [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced physical activity levels can lead to an increased risk of secondary health complications, including worsening physiological and psychosocial health among those with SCI (10). This can negatively impact quality of life and participation in activities of daily living in this population (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined patient satisfaction with online group exercise programmes for specific clinical conditions including spinal cord injury [ 17 ], multiple sclerosis [ 18 ], Parkinson’s disease [ 19 ], pregnancy [ 20 ] and most notably in cardiac rehabilitation programmes [ 21 , 22 ] and pulmonary rehabilitation programmes [ 23 – 26 ]. One of these studies compared satisfaction with OGEPs compared to in-person programmes and found no difference [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies compared satisfaction with OGEPs compared to in-person programmes and found no difference [ 23 ]. Convenience and flexibility were regularly cited as advantages to OGEPs and improved accessibility was regularly cited as an important advantage particularly in the neurological populations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%